Toxicity of selected conventional insecticides against elaeidobius kamerunicus faust (coleoptera: curculionidae) - Che Ghani, Muhammad Farid (2017)
Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae), the pollinating weevil, is the most efficient insect pollinator of oil palm, Elaeis guineensis Jacq. (Arecales: Arecaceae). In Malaysia, it was first introduced in Sabah to assist the pollination of oil palm plantation. The assisted pollination has proven to significantly improve the fruit set development as well as giving the higher yield. In this study, the toxicity of insecticides was evaluated against E.kamerunicus as a non-target insect. The adult weevils were exposed to dry residue at the recommended field rate for 2 hours and the immediate effect of insecticides was observed. Then for the survivorship observation, the adult weevils were left for 2 days period to observe their recovery and mortality rate. Four insecticides were used namely cypermethrin, carbaryl, trichlorfon and Bacillus thurengiensis. The lethality index (0-100) was used as a measurement to compare immediate effect and longer term effects of insecticide exposure on E.kamerunicus. The high value indicates the high degree of immediate mortality and low recovery rate of E.kamerunicus from insecticide exposure. Among four insecticides, cypermethrin, carbaryl and trichlorfon showed a moderate initial efficacy (10% < E0 < 90%), while B.thuringiensis was low in initial efficacy (E0 ≤ 10%). All evaluated insecticides showed increasing efficacy where the percentage of moribund and dead larvae increased by >10% after 2 days. The lethality index for carbaryl was 70.5%, followed by cypermethrin, 67.7%, then trichlorfon with 49.4% and B.thuringiensis 11.6%. Consequently, carbaryl shows the highest toxicity on adult of E.kamerunicus compared with other insecticides.